UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PAEDAGOGIK GURU DI TK SE-KECAMATAN TAMBANG KABUPATEN - Dina Nopriani; Baidarus Baidarus (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2022)
The purpose of this study was to determine the principal's efforts to improve the pedagogical competence of teachers in kindergartens in the mining district of Kampar district. The research method uses a descriptive method with a quantitative approach. The population is 110 teachers with a sample of 25% of the population as many as 27 people. Data collection methods are in the form of observation, documentation, and questionnaires. Data analysis is done by using the percentage technique. The results showed that the principal's efforts in improving the pedagogic competence of teachers in Kindergartens throughout the Tambang District of Kampar Regency were classified as very good. This means that the principal has made maximum efforts in improving the pedagogical competence of teachers in Kindergartens throughout the Tambang District of Kampar Regency. Starting from 1) Planning the activities of education, care, and protection programs, 2) Implementing the education, nurturing, and protection process, 3) Carrying out an assessment of the process and outcomes of education, care and protection.